Palm oil: traditional, recent and potential applications in foods - Nor Aini Idris,; Razali Ismail,; Osman Atil,; Wan Rosnani Awang Isa,; Karimah Ahmad, (Universiti Kebangsaan Malaysia, 2002)
Ninety percent of palm oil and its products are used for edible purposes. Palm oil is obtained from the mesocarp of the palm fruit while palm kernel oil is derived from the flesh of the kernel. Although they come from the same fruit, palm oil and palm kernel oil differ in their physical and chemical characteristics. Palm oil is about 50% saturated and contains mainly palmitic (Ci6:0) and oleic (Ci8:i) acids. Palm kernel oil is more than 80% saturated and contains mainly lauric acid (C12:0). Fractionation process separates palm oil into palm olein (liquid) and palm stearin (solid). A second fractionation gives superolein, palm mid fraction and hard stearin. Similarly fractionation separates palm kernel oil into palm kernel olein and palm kernel stearin. Palm oil and palm olein are widely used for industrial frying of snack foods due to their excellent oxidative stability. They have a long shelf life due to the presence of vitamin E, a powerful natural antioxidant. Palm olein produces less smoking, spattering, foaming and gums compared to polyunsaturated oils such as soyabean and sunflower oils. Palm stearin is used as an ingredient (hard feed stock) in the manufacture of shortenings, margarines and vanaspati. Being naturally semi-solid, it is an excellent choice for the manufacture of semi-solid products such as shortenings, margarines and vanaspati since it can reduce cost and is free form trans fatty acids. Palm oil stabilizes the product in β' form, which is required for good creaming and baking performances. Palm kernel oil and its products, either on its own or in combination with palm oil products are widely used in the manufacture of specialty fats, margarines and spreads. Incorporation of palm kernel oil or its derivatives, particularly in table margarine and spreads improves melting characteristic of the products. Palm kernel oil can be used to some extent in shortenings and vanaspati. Palm oil and palm kernel oil are also used in the manufacture of imitation dairy products. They can replace milkfat in production of ice cream, coffee creamer/whitener, whipping cream, milk, cheese and yogurt. Other food which contain palm oil and palm kernel oil include soup mixes, sardines, baked beans, breakfast cereals, shrimp-paste powder, bouillon, peanut butter and beverages. Palm oil products are also used as a spray opil on biscuits and cream crackers to give a richer taste and an attractive glossy appearance. Future outlook sees new applications of palm oil in pourable margarines, burgers, frankfurters and sausage/bologna. Substitution of animal fat with palm oil will give a low cholesterol meat product. With advances in fractionation technology, it is possible to produce superolein which shows potential for application as a salad oil.